Practice of Knowledge Management for retention of intellectual knowledge in small and medium enterprises - Magableh, Ashraf Khaled (Open Science Journal, 2018)
The research will explore and identify the components of knowledge management including knowledge components, knowledge management process, Information technology (IT) and organization / corporate culture eliciting and depicting tacit and explicit knowledge. Further, the research will include the both qualitative and quantitative research implementing ethnographic methodology and online survey and open-ended interview with relevant intellectuals. Additionally, knowledge management is considered as value added to data, personnel perception, and fundamental of knowledge and the knowledge management process will consist of three distinct sub-processes i.e. create, disseminate, and incorporate. Finally, the report will focus on four distinct divisions of knowledge sub-processes for example knowledge creation and acquisition, knowledge organization and retention, knowledge dissemination, and knowledge utilization to improve the effectiveness and efficiency of small and medium enterprises.